An Efficient Acetalization Method for Biomass‐Derived Furfural with Ethanol Using γ‐Al2O3‐Supported Catalysts. Issue 11 (19th March 2020) - Castellanos‐Blanco, Nahury; Taborda, Gonzalo; Cobo, Martha
Abstract: In this paper, the mono and bimetallic catalysts of Rh, Pt and Ni supported on γ‐Al2 O3 were tested for the selective acetalization of furfural to produce furfural diethyl acetal in a mixture containing furfural diluted in ethanol. Ni1.5 Rh1.5 /γ‐Al2 O3 exhibited the highest catalytic activity among all the tested catalysts, with an 85% furfural conversion and 100% furfural diethyl acetal selectivity at 100 °C and 30 min of reaction. Catalyst characterization showed that Ni1.5 Rh1.5 /γ‐Al2 O3 presented particle sizes smaller than 1.2 nm, and the active metals were partially oxidized (Rh III and Ni II ). A direct correlation between conversion and weak acidity of mono and bimetallic catalysts was obtained. Interestingly, despite exhibiting strong acidity, γ‐Al2 O3 alone was little active in the process, which evidenced the role of the metal in acetalization of furfural into ethanol. In‐situ DRIFTS experiments indicated that furfural is easily adsorbed onto these small particles as Ni δ+ ‐(η 1 ‐O, C‐FFR) and Rh δ+ ‐ethoxide species and rapidly transforms into furfural diethyl acetal and water. The catalyst was recycled four times, with a loss in catalytic activity of approximately 19%. The Ni1.5 Rh1.5 /γ‐Al2 O3 catalyst was also successfully applied in the condensation of a variety of biomass derivatives. Abstract : Proposed reaction mechanism of the acetalization of biomass‐derived furfural (FFR) over γ‐Al2 O3 catalyst for the selective production of biomass‐derived furfural (FDEA: furfural diethyl acetal) with ethanol under neat conditions, in which ethanol was simultaneously employed as reactant and solvent. The catalyst was recycled four times, with a loss in catalytic activity of approximately 19%. The Ni1.5 Rh1.5 /γ‐Al2 O3 catalyst was also successfully applied in the condensation of a variety of biomass derivatives.